Is It Necessary to Extend a Multilevel Posterior Cervical Decompression and Fusion to the Upper Thoracic Spine?. Issue 23 (1st December 2016) - Schroeder, Gregory D.; Kepler, Christopher K.; Kurd, Mark F.; Mead, Loren; Millhouse, Paul W.; Kumar, Priyanka; Nicholson, Kristen; Stawicki, Christie; Helber, Andrew; Fasciano, Daniella; Patel, Alpesh A.; Woods, Barret I.; et al.
Abstract : Study Design: A retrospective cohort analysis. Objective: The aim of this study was to determine if there is a difference in the revision rate in patients who undergo a multilevel posterior cervical fusions ending at C7, T1, or T2-T4. Summary of Background Data: Multilevel posterior cervical decompression and fusion is a common procedure for patients with cervical spondylotic myelopathy, but there is little literature available to help guide the surgeon in choosing the caudal level of a multilevel posterior cervical fusion. Methods: Patients who underwent a three or more level posterior cervical fusion with at least 1 year of clinical follow-up were identified. Patients were separated into three groups on the basis of the caudal level of the fusion, C7, T1, or T2-T4, and the revision rate was determined. In addition, the C2-C7 lordosis and the C2-C7 sagittal vertical axis (SVA) was recorded for patients with adequate radiographic follow-up at 1 year. Results: The overall revision rate was 27.8% (61/219 patients); a significant difference in the revision rates was identified between fusions terminating at C7, T1, and T2-T4 (35.3%, 18.3%, and 40.0%, P  = 0.008). When additional variables were taken into account utilizing multivariate linear regression modeling, patients whose construct terminated at C7 were 2.29 (1.16–4.61) times more likely to require a revision than patients whose construct terminated at T1 ( P  = 0.02), but no difference between stopping at T1 and T2-T4 was identified. Conclusion: Multilevel posterior cervical fusions should be extended to T1, as stopping a long construct at C7 increases the rate of revision. Level of Evidence: 3